Pengembangan Sistem Polikultur Udang Galah Dan Ikan Nila Sebagai Upaya Peluang Komoditas Perikanan Unggulan Dan Meningkatkan Ketahanan Pangan Di Desa Tenjolaya Kabupaten Sukabumi - Eko Rini Rini Farastuti; Ananingtyas S Darmarini; Dewi Anggraeni (Pusat Riset dan Inovasi Nasional, 2025)
The development of a polyculture system combining giant freshwater prawns (Macrobrachium rosenbergii) and tilapia (Oreochromis niloticus) offers an opportunity to increase productivity and local food security by optimizing land and water resource use. This study analyzed the weight and length growth data of giant freshwater prawns (weeks 1–4) and tilapia (weeks 1–6) cultivated in a polyculture system in Tenjolaya Village, Sukabumi Regency. The results showed a positive growth trend for both commodities: giant freshwater prawns increased in average weight from 0.00 g (week 1) to 0.13 g (week 4) and length from 0.98 cm → 1.74 cm; tilapia increased in average weight from 16.90 g (week 1) to 49.97 g (week 6) and length from 7.90 to 15.68 cm. The discussion assesses the technical feasibility of polyculture, its implications for feed efficiency and disease, and its contribution to local food security. Recommendations include stocking density management, water quality management, feed management, and adoption schemes for local farmers. This study confirms that shrimp–tilapia polyculture is a promising technical strategy for improving integrated fisheries production and village food security.